COMPARISONS BETWEEN MEASUREMENT AND CALCULATION METHODS IN OBTAINING VIRTUAL WATER FOR HOME MADE YOGURT - Wijonarko, Sensus; Sirenden, Bernadus; Maftukhah, Tatik; Rustandi, Dadang (Instrumentasi, 2019)
The aim of this study was to get shadow water result comparisons for home industry yogurt using practical and theoretical methods. The embodied water obtained from the empirical technique was 20.2 liters, namely 3.8 liters lower than the mathematical technique. The differences of the embedded water between two methods were caused especially on one side the producer did not optimize the water potential to absorb the heat, but on the other side the producer did not pay any attention to the regulation in disposing the waste water that should not be higher than its threshold level. The consumption of exogenous water could be decreased if the cooling water was recycled, water heat was dissipated using natural air, and the unused milk was consumed by cattle.